Kepemimpinan Dan Teladan Dalam Pelayanan Gerejawi, Kajian Alkitabiah Komunikasi sebagai Urgensi - Lusyana Yosepha Winata (JURNAL LUXNOS, 2026)
The purpose of this study is to emphasize the importance of communication in church leadership to enhance synergy in ministry. The background of this research is the understanding that Christian leadership must be centered on the example of Jesus. A common problem is that modern leaders tend to be unable to communicate effectively. Yet, the most important thing to implement in today's ministry is a model of communicative leadership, like that of Jesus. Jesus' example always emphasized the values ​​of love, obedience, service, and, of course, God's will in building harmonious working relationships within the church. Communication is not merely a medium for conveying information but must also be a strategic tool for building trust and unity in ministry. This research used a qualitative method with a literature study approach that examined theological sources and contextual Christian leadership. The results show that effective communication plays a significant role in creating solid cooperation, synergy, shared understanding, and especially in strengthening integrity and solidarity in ministry. In addition to empathy, openness in interactions and a leader's ability to establish constructive communication channels is crucial. Therefore, effective communication in leadership plays a central role in supporting team performance, spiritual growth, the quality of cooperation in church life, and strengthening integration in church ministry in particular and secular ministry in general.